Challenges of scaling up and of knowledge transfer in an action research project in Burkina Faso to exempt the worst-off from health care user fees - Kadio Kadidiatou; Kafando Yamba; Yaogo Maurice; Ridde Valéry; Ouedraogo Moctar; Sanfo Marou; Coulibaly Norbert; Bicaba Abel; Haddad Slim (BMC, 2011)
Abstract Background Systems to exempt the indigent from user fees have been put in place to prevent the worst-off from being excluded from health care services for lack of funds. Yet the implementation of these mechanisms is as rare as the operational research on this topic. This article analyzes an action research project aimed at finding an appropriate solution to make health care accessible to the indigent in a rural district of Burkina Faso. Research This action research project was initiated in 2007 to study the feasibility and effectiveness of a community-based, participative and financially sustainable process for exempting the indigent from user fees. A interdisciplinary team of researchers from Burkina Faso and Canada was mobilized to document this action research project. Results and knowledge sharing The action process was very well received. Indigent selection was effective and strengthened local solidarity, but coverage was reduced by the lack of local financial resources. Furthermore, the indigent have many other needs that cannot be addressed by exemption from user fees. Several knowledge transfer strategies were implemented to share research findings with residents and with local and national decision-makers. Partnership achievements and difficulties Using a mixed and interdisciplinary research approach was critical to grasping the complexity of this community-based process. The adoption of the process and the partnership with local decision-makers were very effective. Therefore, at the instigation of an NGO, four other districts in Burkina Faso and Niger reproduced this experiment. However, national decision-makers showed no interest in this action and still seem unconcerned about finding solutions that promote access to health care for the indigent. Lessons learned The lessons learned with regard to knowledge transfer and partnerships between researchers and associated decision-makers are: i) involve potential users of the research results from the research planning stage; ii) establish an ongoing partnership between researchers and users; iii) ensure that users can participate in certain research activities; iv) use a variety of strategies to disseminate results; and v) involve users in dissemination activities.